The role of macrophage-myofibroblast transition in the pathogenesis of multi-organ fibrosis - Congcong Guo; Ran Cao; Lin Liao; Junyu Zhao; Tianzuo Wang; Junhan Li; Yue Zhang; Haotian Li (Tissue and Cell, 2026)

BcSak1-mediated adaption to low temperature in Botrytis cinerea represents optional targets for management of cold-tolerant diseases on harvested fruits - Ziwei Su; Yuxuan Lin; Xinyi Long; Jiaxi Zhang; Yin Li; Chuanxi Zhu; Wenjin Yan; Congcong Wang; Yiwen Wang; Junwei Zhao; Xiang Li; Aruppillai Suthaparan; et al. (Postharvest Biology and Technology, 2026)

Dual isoflavone and carboxyl-containing compound profiling for antioxidant evaluation of fermented soybean products - Yuetong Jiang; Yuye Gao; Xiaojing Liu; Congcong Gao; Wen Yang; Tian Tian; Yujia Zhai; Fangyuan Gao; Yunxia Li; Wenjing Zhang; Zhi Chai; Jian-lin Wu; et al. (Food Research International, 2026)

Deciphering the long-term performance and underlying mechanisms of an engineering-scale anaerobic-anoxic-oxic-anaerobic-vibrating MBR process - Shujuan Che; Weichen Lin; Haojie Ding; Congcong Zhang; Xiangyu Li; Kaichang Yu; Huanhuan Guan; Jie Shi; Yun Yang; Xia Huang (ENGINEERING Environment, 2026)

Chilling tolerance in kiwifruit alleviated by brassinosteroid: roles in ROS scavenging, membrane lipid stabilization, and energy metabolism - Yupei Zhang; Lin Shen; Zhenyu Huang; Congcong Yang; Caining Yang; Kangyuan Xie; Huaxuan Hu; Chuying Chen; Yingying Yang; Ming Chen; Wenbin Kai; Jiaoke Zeng; et al. (Food Chemistry, 2026)

Erratum to “The role of macrophage-myofibroblast transition in the pathogenesis of multi-organ fibrosis” [Tissue Cell 103 (2026) 103702] - Congcong Guo; Ran Cao; Lin Liao; Junyu Zhao; Tianzuo Wang; Junhan Li; Yue Zhang; Haotian Li (Tissue and Cell, 2026)

Dipole driven interfacial coupling in COF/Bi2Fe4O9 S-scheme heterojunctions greatly boosts PMS activation for neonicotinoids degradation - Sai Bai; Wenzhen Lu; Lin Yang; Congcong Duan; Zhixuan Wang; Yan Shao; Tianjiao Xia; Lingyan Zhu (Journal of Hazardous Materials, 2026)

Integration of local climatic factors and global climate oscillations for enhanced monthly precipitation forecasting in the Asian monsoon region - Congcong Li; Lulu He; Lin Luo; Dan Liu; Junxia Liao (Theoretical and Applied Climatology, 2026)

Adsorption of perfluorocarboxylic acids by carbon nanotube and its derivative: Insight into mechanisms based on experimental study and modeling analysis - Lin Yang; Zhixuan Wang; Congcong Duan; Yan Shao; Tianjiao Xia (Chemosphere, 2026)

Multi-objective hierarchical reinforcement learning for efficient and safe robotic manure cleaning in dairy barns - Wei Wei; Congcong Sun; Lin Wu; Jianglin Lan (Computers and Electronics in Agriculture, 2026)

Characterization and comparison of the structure and antioxidant activity of queen bee larvae (Apis mellifera) hydrolysates processed with different proteases - Lili Pang; Fangfang Yan; Aibo Wu; Congcong Lin; Ruonan Liu; Qun Lu; Rui Liu (Food Chemistry, 2026)

A dual-functional nanomaterial for high-capacity uranium(VI) adsorption and rapid fluorescence detection in water - Sha Yang; Xuanzhe Liao; Zhiyu Hou; Yuxin Zhang; Congcong Ding; Ling Ding; Jun Liao; Lielin Wang; Lin Zhang (Process Safety and Environmental Protection, 2026)

Exploring efficient mainstream nitrogen removal by partial nitrification/anammox under limited COD condition in a pilot-scale membrane aerated biofilm reactor - Lisheng Wang; Congcong Zhang; Xiaofeng Kang; Yanchen Liu; Yong Qiu; Deqing Wanyan; Jiayin Liu; Gang Cheng; Pengfei Lin; Xia Huang (Water Research, 2026)

Efficient uranium adsorption performance of TiO2 nanoparticles through the bridging effect of SiO2 and the high selectivity of amidoxime - Sha Yang; Zhengqi Yang; Zhiyu Hou; Jun Liao; Lielin Wang; Congcong Ding; Lin Zhang (Journal of Water Process Engineering, 2026)

Widely targeted metabolomics reveals the phenolic profiles of Lentinula edodes and its correlation with antioxidant activity - Qiongdan Zhang; Qi Tao; Congcong Lin; Xiang Yan; Hongshan Liang; Qun Lu (Food Bioscience, 2026)

Dynamic cross-linked/conductive dual-network polyurethane for integrated EMI shielding, thermal management and motion sensing - Sijie Yu; Taotao Qiang; Xiaoyong Dong; Congcong Lin; Xiaonan Ruan; Guannan Dong; Haiyang Hu; Fangfang Dong; Chen Mi; Tianlin Chen; Chen Zhang; Longfang Ren (Chemical Engineering Journal, 2026)

Soil microbiomes in urban green spaces: Foundation of ecosystem functions and human health - Xiao-Tong Zhu; Xi-Lin Yuan; Pin Li; Congcong Shen (Soil Ecology Letters, 2026)

Catalytic application of coal liquefaction bottom residue in co-hydrocracking with MRAR under catalyst-free conditions - Zefeng Miao; Tengfei Yang; Congcong Liu; Yao Jiang; Lin Meng; Huitao Liu; Xiaobin Wang; Chuan Li (Fuel, 2026)

Fluvoxamine Attenuates Blood–Brain Barrier Disruption in Drug-Resistance Epilepsy and inhibits Ferroptosis via the Sigma-1 Receptor-TAMM41 signaling in bEnd.3 cells - Lin Guo; Siyu Liu; Na Lv; Jianlun Ji; Xinting Lin; Ying Ke; Zhidong Liu; Congcong Sun; Yun Wang (Molecular Neurobiology, 2026)

Embryonic exposure to nanoplastics affects the metabolism and locomotor performance of a soil-dwelling, oviparous skink - Xinni He; Jiahui Xu; Shufang Zhang; Mengzhen Hu; Congcong Wang; Miao Guan; Peng Li; Lian Chen; Longhui Lin; Georgia Ward-Fear; Hong Li (Environmental Pollution, 2025)

Magnetic-field-assisted fabrication of Fe3O4-enhanced thin-film nanocomposite polyamide nanofiltration membranes with enhanced separation performance - Congcong Zhou; Zhihao Chen; Jingfen Yuan; Yang Jiao; Hongjun Lin; Yanchao Xu (Desalination, 2025)

Templating PbI2 intermediate phase toward crystal-plane-engineered formamidinium-based perovskite films for efficient and stable solar cells - Yanzhuo Gou; Jiaqi Zhang; Jinguo Cao; Weideren Dai; Wenbo Li; Bowen Jin; Yun Wang; Liangyou Lin; Congcong Wu; Tao Mei; Xianbao Wang; Qidong Tai; et al. (Chemical Engineering Journal, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Tree-ring dating of the construction of the Yinshan tomb in Shaoxing, Zhejiang Province: A preliminary study - Shiyuan Shi; Congcong Xiao; Zebin Li; Yongxiang Wang; Hui Wang; Zhansheng Niu; Hongyan Zhang; Pengyu Lin; Xinrui Liu; Lingling Lu; Jiangfeng Shi; Huayu Lu (Science China Earth Sciences, 2025)

Multi-omics joint analysis: Pachymic acid ameliorated non-alcoholic fatty liver disease by regulating gut microbiota - Guilin Ren; Yiyou Lin; Yilong Fu; Fucai Liu; Ruiqi Wang; Congcong Zhang; Jiannan Qiu; Lin Chen; Xiaobing Dou (Food Research International, 2025)

The 14–3–3 gene AaGRF1 positively regulates cold tolerance in kiwifruit - Zhang Zhenzhen; Li Sumei; Sun Shihang; Li Hongli; Zhang Qina; Li Yihang; Li Yukuo; Liu Mingyu; Li Congcong; Sun Leiming; Lin Miaomiao; Qi Xiujuan (Plant Science, 2025)

Achieving mainstream nitrogen removal by partial nitrification and anammox in the carriers-coupled membrane aerated biofilm reactor - Lisheng Wang; Congcong Zhang; Yanchen Liu; Yong Qiu; Deqing Wanyan; Jiayin Liu; Gang Cheng; Pengfei Lin; Xia Huang (Water Research, 2025)

Diamide insecticides in PM2.5: The unreported rural and urban air pollutants - Yanhao Zhang; Zifang Peng; Peiru Luo; Lin Zhu; Qingyun He; Congcong Pei; Dan Yin; Wenfen Zhang; Shusheng Zhang; Zongwei Cai (Journal of Hazardous Materials, 2025)

Specific Mode Electroacupuncture Stimulation Mediates the Delivery of NGF Across the Hippocampus Blood–Brain Barrier Through p65-VEGFA-TJs to Improve the Cognitive Function of MCAO/R Convalescent Rats - Mengyuan Dai; Kecheng Qian; Qinyu Ye; Jinding Yang; Lin Gan; Zhaoxing Jia; Zixing Pan; Qian Cai; Tianxiang Jiang; Congcong Ma; Xianming Lin (Molecular Neurobiology, 2025)
Cognitive impairment frequently presents as a prevalent consequence following stroke, imposing significant burdens on patients, families, and society. The objective of this study was to assess the effectiveness and underlying mechanism of nerve growth factor (NGF) in treating post-stroke cognitive dysfunction in rats with cerebral ischemia–reperfusion injury (MCAO/R) through delivery into the brain using specific mode electroacupuncture stimulation (SMES). From the 28th day after modeling, the rats were treated with NGF mediated by SMES, and the cognitive function of the rats was observed after treatment. Learning and memory ability were evaluated using behavioral tests. The impact of SMES on blood–brain barrier (BBB) permeability, the underlying mechanism of cognitive enhancement in rats with MCAO/R, including transmission electron microscopy, enzyme-linked immunosorbent assay, immunohistochemistry, immunofluorescence, and TUNEL staining. We reported that SMES demonstrates a safe and efficient ability to open the BBB during the cerebral ischemia repair phase, facilitating the delivery of NGF to the brain by the p65-VEGFA-TJs pathway. Graphical Abstract By Figdraw

Cold tolerance of postharvest fungal pathogens is regulated by the conserved high osmolarity glycerol (HOG) pathway - Wenjin Yan; Ziwei Su; Ganghan Zhou; Yuxuan Lin; Weiheng Ren; Jinglei Liao; Chuanxi Zhu; Congcong Wang; Dandan Ren; Yiwen Wang; Aruppillai Suthaparan; Ling Xu; et al. (Postharvest Biology and Technology, 2025)

Geochemical study of UHP serpentinites in southwestern Tianshan, China and its implications for trace elements deep recycling - Tingting Shen; José Alberto Padrón-Navarta; Thomas Bader; Congcong Lin; Tian Qiu; Jingsui Yang (Lithos, 2025)

Mitochondrial Protein TAMM41 Modulates Depressive-like Behaviors - Lin Guo; Ziyu Liu; Xiaoxia Jia; Qinghua Wang; Jianlun Ji; Na Lv; Zhidong Liu; Qin Zhou; Congcong Sun; Yun Wang (Molecular Neurobiology, 2024)

Effects of tourism development on ecological network and function of sediment microbial communities in the urban wetland park - Binhao Wang; Kaiming Hu; Lin Chen; Wei Zhang; Congcong Zhang; Wenbing Li; Hangjun Zhang (Soil Ecology Letters, 2024)

Direct recovery of high-purity lithium via nanofiltration membranes from leaching solution of spent lithium batteries - Shiweihua He; Qiuyang Zuo; Hui Shi; Zhiwei Geng; Congcong Liu; Lin Ding; Xin Li; Penghui Shao; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2024)

Saline-alkali land reclamation boosts topsoil carbon storage by preferentially accumulating plant-derived carbon - Lin Chen; Guixiang Zhou; Biao Feng; Chao Wang; Yu Luo; Fang Li; Congcong Shen; Donghao Ma; Congzhi Zhang; Jiabao Zhang (Science Bulletin, 2024)

Habitat differentiation and environmental adaptability contribute to leaf size variations globally in C3 and C4 grasses - Wuchao Gao; Dachuan Dai; Huan Luo; Dongli Yu; Congcong Liu; Ning Zhang; Lin Liu; Chengming You; Shixing Zhou; Lihua Tu; Yang Liu; Congde Huang; et al. (Science of The Total Environment, 2024)

Enzymatic modular synthesis of asymmetrically branched human milk oligosaccharides - Yinshuang Li; Yi Li; Yuxi Guo; Congcong Chen; Lin Yang; Qian Jiang; Peixue Ling; Shuaishuai Wang; Lei Li; Junqiang Fang (Carbohydrate Polymers, 2024)

Discovery of the tigecycline resistance gene cluster tmexCD3-toprJ1 in Pasteurella multocida strains isolated from pigs in China - Congcong Shi; Zhanwei Zhu; Yuyao Shang; Wenbo Song; Jie Yang; Haixin Bi; Zihao Wang; Rui Xie; Mengfei Zhao; Lin Hua; Huanchun Chen; Bin Wu; et al. (Veterinary Microbiology, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

Asymmetric wettable three-dimensional Janus all-cellulose aerogel: Controllable construction with a similar phase self-assembling strategy and oil-water separation performance - Jingjing Zhang; Congcong Wang; Zhibo Lin; Qian Fu; Chenxi Niu; Zaowen Zhao; Lingbin Lu (Journal of Environmental Chemical Engineering, 2023)

Carboxyl-containing components delineation via feature-based molecular networking: A key to processing conditions of fermented soybean - Yuye Gao; Yu Fu; Na Li; Yuetong Jiang; Xiaojing Liu; Congcong Gao; Lishuang Wang; Jian-Lin Wu; Tingting Zhou (Food Chemistry, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

Prohibitin Protein Expression During Spermatogenesis in the Large Yellow Croaker, Larimichthys crocea - Chenwen Lin; Xinming Gao; Jie Ni; Shengshuo Zhang; Cheng Liu; Shengyu Luo; Chen Du; Xuebin Zheng; Congcong Hou; Daojun Tang; Chundan Zhang; Junquan Zhu (Journal of Ocean University of China, 2022)

Study on In-seam Wave Response Characteristics of Reflection in Fault Bearing Coal Seam of Shuangliu Coal Mine - Lei Zhang; Lin Xu; Zhulin Wei; Congcong Feng (Geotechnical and Geological Engineering, 2022)

Shifts in the bacterial community along with root-associated compartments of maize as affected by goethite - Peduruhewa H Jeewani; Lin Chen; Lukas Van Zwieten; Congcong Shen; Georg Guggenberger; Yu Luo; Jianming Xu (Biology and Fertility of Soils, 2020)

A Facile and Sensitive DNA Sensing of Harmful Algal Blooms Based on Graphene Oxide Nanosheets - Le Qiang; Yu Zhang; Chao Wu; Yingkuan Han; Suchun Wang; Yanyan Wang; Congcong Zhang; Guangzhou Liu; Qi Wu; Hong Liu; Ian R. Jenkinson; Jun Sun; et al. (Marine Biotechnology, 2020)

Negative effects of rare earth oxide nanoparticles of La2O3, Nd2O3, and Gd2O3 on the ammonia-oxidizing microorganisms - Yan Yue; Lin Qi; Yan Li; Jichen Wang; Congcong Shen; Yuan Ge (Journal of Soils and Sediments, 2020)

Endothelial Notch activation promotes neutrophil transmigration via downregulating endomucin to aggravate hepatic ischemia/reperfusion injury - Peiran Zhang; Kangyi Yue; Xinli Liu; Xianchun Yan; Ziyan Yang; Juanli Duan; Congcong Xia; Xinyuan Xu; Mei Zhang; Liang Liang; Lin Wang; Hua Han (Science China Life Sciences, 2020)

Effect of bisphosphonates on overall survival in subgroups of patients with prostate cancer - Congcong Wu; Wenjun Chen; Jian Wu; Xi Zhang; Xuanzhang Huang; Ruifang Lin; Baoling Zhu; Hua Jiang (Clinical & Experimental Metastasis, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Contrasting elevational diversity patterns between eukaryotic soil microbes and plants - Congcong Shen; Wenju Liang; Yu Shi; Xiangui Lin; Huayong Zhang; Xian Wu; Gary Xie; Patrick Chain; Paul Grogan; Haiyan Chu (Ecology, 2014)
The diversity of eukaryotic macroorganisms such as animals and plants usually declines with increasing elevation and latitude. By contrast, the community structure of prokaryotes such as soil bacteria does not generally correlate with elevation or latitude, suggesting that differences in fundamental cell biology and/or body size strongly influence diversity patterns. To distinguish the influences of these two factors, soil eukaryotic microorganism community structure was investigated in six representative vegetation sites along an elevational gradient from forest to alpine tundra on Changbai Mountain in Northeast China, and compared with our previous determination of soil bacterial community structure along the same gradient. Using bar‐coded pyrosequencing, we found strong site differences in eukaryotic microbial community composition. However, diversity of the total eukaryotic microorganism community (or just the fungi or protists alone) did not correlate with elevation. Instead, the patterns of diversity and composition in the total eukaryotic microbial community (and in the protist community alone) were closely correlated with soil pH, suggesting that just as for bacteria, acidity is a particularly important determinant of eukaryotic microbial distributions. By contrast, as expected, plant diversity at the same sites declined along our elevational gradient. These results together suggest that elevational diversity patterns exhibited by eukaryotic microorganisms are fundamentally different from those of plants.

miR-124 Represses ROCK1 Expression to Promote Neurite Elongation Through Activation of the PI3K/Akt Signal Pathway - Xi Gu; Siying Meng; Shuhu Liu; Chunhong Jia; Yingying Fang; Shuji Li; Congcong Fu; Qiancheng Song; Lifang Lin; Xuemin Wang (Journal of Molecular Neuroscience, 2014)

Ex-situ enzyme activity and bacterial community diversity through soil depth profiles in penguin and seal colonies on Vestfold Hills, East Antarctica - Dawei Ma; Renbin Zhu; Wei Ding; Congcong Shen; Haiyan Chu; Xiangui Lin (Polar Biology, 2013)

Molecular mechanism of elicitor-induced tanshinone accumulation in Salvia miltiorrhiza hairy root cultures - Guoyin Kai; Pan Liao; Hui Xu; Jing Wang; Congcong Zhou; Wei Zhou; Yaping Qi; Jianbo Xiao; Yuliang Wang; Lin Zhang (Acta Physiologiae Plantarum, 2012)